Golden Inspirations: using Motivational Videos to make a Positive Difference in the Lives of Seniors - Ali, Sonila; Shah, Ibrahim; Memon, Samreen; Ara, Anjum (Journal of World Science, 2023)
In the current era, the advent of digital media has significantly altered how individuals establish connections and seek sources of inspiration. Inside this context, a noteworthy avenue arises known as "Golden Inspirations," which harnesses the power of motivational videos to skillfully construct a framework of optimism and personal growth in the lives of older adults. The objective of this study was to examine the relationship between life satisfaction and psychological wellness, as well as the influence of motivational movies on these variables. This study was done on 82 senior citizens of the Al Azhar Garden Society. A survey was conducted through the life satisfaction scale and psychological well-being scale before and after the motivational video. The result for this study was a mean average of 21.40 before videos and 24.15 after videos for the life satisfaction scale. Similarly, the mean average was 0.84 before and 1.57 after the videos for psychological well-being. The determinants of life satisfaction among older individuals encompass various social, physical, mental, and financial dimensions. These factors are likely to interact with one another, particularly about experiences of loneliness, level of self-care ability, overall health status, feelings of distress, and inadequate financial resources relative to one's needs. To preserve the life pleasure of an individual, it is imperative to consider these many aspects.